Chemotherapy for Hodgkin's lymphoma in a patient receiving clozapine for treatment-resistant schizophrenia: use of the Mental Capacity Act 2005. (December 2015) - Chamberlain, Florence Elizabeth; Walsh, Nicholas; Falkowski, Jan
Summary: Treatment resistance occurs in approximately 30% of individuals with schizophrenia and is commonly treated with clozapine. Nodular sclerosing Hodgkin's lymphoma is a subtype of Hodgkin's lymphoma predominantly affecting those under 50 years of age. In this case report, an individual with treatment-resistant schizophrenia developed nodular sclerosing Hodgkin's lymphoma and is treated with concurrent clozapine and systemic chemotherapy. The aim of this case report is to act as guidance for clinicians and to outline the difficulties of treating individuals with psychiatric illness under the Mental Capacity Act 2005 when the proposed treatment could lead to high levels of morbidity and mortality.